A comparison study of Taiwan regulation and GHTF regulatory model on in vitro diagnostic medical devices. (3rd April 2017) - Tsai, Wen-Wei; Tu, Pei-Weng; Lin, Hsin-Hui; Wang, Yin-Hsuan; Wu, Shiow-Ing; Fan, Yin-Ting
ABSTRACT: Introduction : In Taiwan, In Vitro Diagnostic Medical Device (IVD) is regulated as medical device since 1987, and the implementation of IVD registration was fully completed in 2005. The management system of IVD medical device is highly similar with a guidance 'The GHTF Regulatory Model' developed by Global Harmonization Task Force (GHTF) in 2011 for use of regulation development on medical devices. Area covered : In this study, the Regulatory Model developed by GHTF was compared with Taiwanese IVD management system and it has shown that these two regulatory frameworks are highly similar. Expert commentary : The experience of IVD management in Taiwan can serve a strong evidence to prove the feasibility and effectiveness of GHTF Regulatory Model.